Management of Inclusive Learning in Growing PAUD Inclusion Tegalrejo Yogyakarta - Mukhtar, Zulfadhly (ACIECE, 2019)
Education has become a basic need for every child, both children who do not have special needs (normal) or children with special needs. Inclusive learning provides answers to phenomena that have existed so far. To that end, the implementation of inclusive learning is inseparable from a management in terms of regulating the course of learning activities. This research was conducted aiming to find out and study how the management of inclusive learning carried out in Growing PAUD Inclusion Tegalrejo Yogyakarta. The research method used in this study is a qualitative research method. Data collection techniques used were observation, interviews, and documentation. Data validity test used is source triangulation technique. Furthermore, the data collected was analyzed descriptively qualitatively with interactive analysis techniques consisting of data reduction, data presentation, and drawing conclusions. The results showed that inclusive education management in Growing PAUD Inclusion in Tegalrejo Yogyakarta was carried out in four stages, namely: (1) learning planning, (2) organizing learning, (3) implementing learning, and (4) learning assessment. Based on the results of the study it can be concluded that inclusive learning is carried out by taking into account all aspects of the needs and potential of children. Inclusive learning management that is run in Growing PAUD Inclusion is not much different from regular education management in general. Management of Inclusive Learning in Growing PAUDInclusion is carried out in accordance with management functions, namely: learning planning,organizing learning, implementing learning, and evaluating learning. The difference only lies in the learning objectives that will be set, stimulus, and treatment given to children in accordance with the child's condition in general and specifically. So there is a separation of learning objectives in a learning activity that is tailored to the needs of children, both for children with special needs and for normal children